The liberation of the camps the end of the Holocaust and its aftermath - Stone, Dan 1971- (New Haven London Yale University Press, 2015)
Introduction: explaining liberation -- Liberated by the Soviets -- The Western allies -- Out of the chaos -- Displaced persons (dps) or betrayed persons (bps)? life in the dp camps -- Transitions: dps in a changing world -- Conclusion: the sorrows of liberation
Introduction: explaining liberationLiberated by the Soviets -- The Western allies -- Out of the chaos -- Displaced persons (dps) or betrayed persons (bps)? life in the dp camps -- Transitions: dps in a changing world -- Conclusion: the sorrows of liberation.
Literaturverzeichnis: Seite 242-263
Archivierung/Langzeitarchivierung gewährleistet
Archivierung/Langzeitarchivierung gewährleistet
Keywords: World War, 1939-1945 -- Concentration camps -- Liberation; Concentration Camps -- Europe -- History -- 20th century; Holocaust, Jewish (1939-1945); World War, 1939-1945 -- Refugees; World War, 1939-1945 -- Jews